2017
DOI: 10.1007/s00426-017-0860-z
|View full text |Cite
|
Sign up to set email alerts
|

On the time-course of automatic response activation in the Simon task

Abstract: The Simon effect (prolonged RT when the task-irrelevant stimulus location is incongruent with the response side) has been reported to decrease at longer RTs, which is reflected in negative-going delta functions. This finding has been attributed to gradual dissipation of the response automatically activated by the task-irrelevant location information. The Diffusion Model for Conflict Tasks (DMC, Ulrich, Schröter, Leuthold, & Birngruber, Cognitive Psychology 78:148-174, 2015) formally specifies the time-course o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…The location-based Simon effect was obtained on mean RT, and the effect decreased as RT increased in the Vincentile analyses, replicating findings obtained in previous studies (Ansorge & Wühr, 2004;Pratte et al, 2010;Proctor et al, 2009;Ellinghaus et al, 2017). The location-based Simon effect of 21 ms was similar to Ellinghaus et al's Experiment 1 (22 ms) and Experiment 2 (24 ms), in which the location-based Simon effect on mean RTand delta functions were invariant against changes of stimulus duration (150 ms or until response emitted).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The location-based Simon effect was obtained on mean RT, and the effect decreased as RT increased in the Vincentile analyses, replicating findings obtained in previous studies (Ansorge & Wühr, 2004;Pratte et al, 2010;Proctor et al, 2009;Ellinghaus et al, 2017). The location-based Simon effect of 21 ms was similar to Ellinghaus et al's Experiment 1 (22 ms) and Experiment 2 (24 ms), in which the location-based Simon effect on mean RTand delta functions were invariant against changes of stimulus duration (150 ms or until response emitted).…”
Section: Discussionsupporting
confidence: 88%
“…In studies using a Vincentizing procedure (Ratcliff, 1979), a group RT distribution is obtained by partitioning each participant's RTs on the corresponding and noncorresponding trials into percentile bins (e.g., 10), ranging from shortest to longest, and the Simon effect (the difference) is calculated for each bin. Most findings are that the location-based Simon effect is largest for fast responses but decreases, and even may reverse, as responses slow when the imperative stimulus is displayed in a left or right location (Ansorge & Wühr, 2004;Ellinghaus, Karlbauer, Bausenhart, & Ulrich, 2017;Pratte, Rouder, Morey, & Feng, 2010;Servant, Montagnini, & Burle, 2014;Ulrich et al, 2015). In contrast, the word-and arrow-based Simon effects increase as RTs increase (Miles & Proctor, 2012;Pellicano et al, 2009;Proctor et al, 2009).…”
Section: Response-time Distribution and Chronometric Analysesmentioning
confidence: 99%
“…The experimental setup to test dual-joystick directional responses to vibrotactile stimuli presented in this work can be also considered as a Stimulus-Response Compatibility (SRC) test [38] [39] [40]. For this purpose, it is possible to take into account the accuracy and correct responses reaction times in the different directions and to analyse the compatibility or incompatibility between stimuli and responses in the four different conditions.…”
Section: Stimulus-response Compatibilitymentioning
confidence: 99%
“…The time-course of these processes has been investigated through analysis of the reaction time (RT) distributions (De Jong et al, 1994;Ellinghaus, Karlbauer, Bausenhart, & Ulrich, 2017;Proctor, Miles, & Baroni, 2011;Ridderinkhof, 2002). This technique has revealed that the direct (unconditional) response activation occurs soon after the stimulus onset and then dissipates over time leading to a decrease of the Simon effect as RT increases (e.g., Ellinghaus et al, 2017;Proctor, Yamaguchi, Zhang, & Vu, 2009;Rubichi & Pellicano, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The time-course of these processes has been investigated through analysis of the reaction time (RT) distributions (De Jong et al, 1994;Ellinghaus, Karlbauer, Bausenhart, & Ulrich, 2017;Proctor, Miles, & Baroni, 2011;Ridderinkhof, 2002). This technique has revealed that the direct (unconditional) response activation occurs soon after the stimulus onset and then dissipates over time leading to a decrease of the Simon effect as RT increases (e.g., Ellinghaus et al, 2017;Proctor, Yamaguchi, Zhang, & Vu, 2009;Rubichi & Pellicano, 2004). However, there are other instances where the Simon effect increases or remain stable such as in the standard left-right auditory Simon task, when responses are made with crossed hands and, when the stimulus and response locations are arrayed vertically rather than horizontally (Vallesi, Mapelli, Schiff, Amodio, & Umiltà, 2005;Wascher, Schatz, Kuder, & Verleger, 2001;Wühr, 2006, but see Xiong & Proctor, 2016).…”
Section: Introductionmentioning
confidence: 99%